Are Metal Complexes "Organic, " "Inorganic, " "Organometallic, " or "Metal-Organic" Materials? A case Study for the Use of Trinuclear Coinage Metal Complexes as "Metal-Organic Coatings" for Corrosion Suppression on Aluminum Substrates. Issue 1 (2nd January 2019) - Yaseen, Waleed K.; Sanders, Stephen F.; Almotawa, Ruaa M.; Otten, Brooke M.; Bhat, Sonali; Alamo, Domllermut C.; Marpu, Sreekar B.; Golden, Teresa D.; Omary, Mohammad A.
Abstract : This article provides a second manifestation of a new tradition by which the editors of Comments on Inorganic Chemistry wish to lead by example, whereby we start publishing original research content that, nonetheless, preserves the Journal's identity as a niche for "critical discussion of the current literature" of inorganic chemistry. (For the first manifestation, see: Otten, B. M.; Melancon, K. M.; Omary, M. A. "All That Glitters is Not Gold: A Computational Study of Covalent vs Metallophilic Bonding in Bimetallic Complexes of d 10 Metal Centers—A Tribute to Al Cotton on the 10th Anniversary of His Passing, " Comments Inorg. Chem . 2018, 38, 1–35.) Thus, herein we show that a trinuclear copper (I) complex {[3, 5-(CF3 )2 Pz]Cu}3 (henceforth referred to as the "Cu trimer") can act as a "metal-organic coating" for corrosion protection of aluminum, whereas its silver analogue, {[3, 5-(CF3 )2 Pz]Ag}3 (i.e., the "Ag trimer"), could not. The manuscript was initially submitted to journals that usually publish on "organic coatings" but was rejected on the premise that a metal complex cannot be considered "organic" unless it is incorporated into a polymer. This issue is commented upon herein in the broader context of whether to consider metal complexes "organic, " "inorganic, " "organometallic, " or "metal-organic" materials with manifestations of the use of each classification in the literature. We have found that, upon coating the Cu trimer onto an aluminum (AA 3003) surface, potentiodynamic polarization results in 3.5% NaCl show an increase in corrosion potential (Ecorr ) by ~ 0.6 V concomitant with a three-order-of-magnitude decrease in corrosion current density (icorr ) from 0.025 µA/cm 2 for uncoated aluminum to ~ 9.6 × 10 –5  µA/cm 2 for the Cu trimer-coated surface. With a double coating, the Cu trimer formed a completely insulating surface with no current flow, even at very high potential magnitude and range. Open circuit potential was used to study the stability of the Cu trimer films on the Al surface in the electrolyte solution. Scanning electron microscopy and Fourier-transform infrared spectroscopy techniques were used to characterize the structure of both the Cu trimer powder and Cu trimer film on the aluminum surface before and after the corrosion tests. The hydrophobicity of the Cu trimer coating was determined by using water drop contact angle measurements, which demonstrated an increase from 65° to 137° for the uncoated and coated aluminum, respectively. The thermal stability of the Cu trimer was analyzed using thermogravimetric analysis, giving rise to weight loss resistance up to ~190 °C. The results clearly demonstrate that the Cu trimer layers exhibit superior stability and potential for corrosion protection of aluminum surfaces in corrosive environments. The Ag trimer analogue, meanwhile, failed the "tape test" that the Cu trimer passed to assess the mechanical stability of such "metal-organic" coatings. Density functional theory (DFT) simulations provide insights on this difference upon modeling the interaction of each cyclotrimer molecule (and other analogous ones) with an Al atom on the one hand and contrasting the resulting binding energies with the corresponding dissociation energies of the metallophically-bound crystalline solid form of each trimer. Thus, it was found that Ag trimer models are bound to the Al atom at least as strongly as Cu trimer models are; yet, that bonding is not sufficiently high so as to overcome the argentophilic attraction, whereas it can overcome the cuprophilic attraction. Other explanations are also given to account for trimer interactions with aluminum oxide as well as partial oxidation of only the Cu trimer, which strengthens the interaction with the Al atom. Graphical Abstract: